Discovering otters - Banks, Martin, 1936- (New York : Bookwright Press, 1988)
An introduction to the physical characteristics, habits, and natural environment of both the sea and freshwater otter. Also discusses the different types found around the world and what is being done to assure their survival.
Includes index.
Bibliography: p. 45.
School Library Journal.
Book Links (A.L.A.).
4.7
3-6
Keywords: Otters -- Juvenile literature; Otters; Otters; Otters